2020
DOI: 10.3390/plants9080926
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Content of Some Groups of Phenolic Compounds and Biological Activity of Extracts of Various Parts of Heather (Calluna vulgaris (L.) Hull) at Different Growth Stages

Abstract: Heather (Calluna vulgaris (L.) Hull.) is noted for a diverse chemical composition and a broad range of biological activity. The current study was aimed at monitoring changes in the accumulation of certain groups of phenolic compounds in various organs of heather (leaves, stems, roots, rhizomes, flowers, and seeds) at different growth stages (vegetative, floral budding, flowering, and seed ripening) as well as studying antioxidant (employing the DPPH and FRAP assays) and antibacterial activity of its extracts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 54 publications
(67 reference statements)
2
27
0
Order By: Relevance
“…These results correlate with those found in Geoffroea decorticans extracts, in which leaves showed higher levels of HCA derivatives when compared to stems [33]. Chapel [16], working with Calluna vulgaris (L.) Hull, reported that the higher amounts of polyphenolic compounds, including HCA, were found in stems and leaves at all phenological stages except during flowering, while no significant differences in PA content were observed among different organs and phenological stages. As in L. cuneifolia, PA were also found in adult plants of the Mexican mistletoes Phoradendron bollanum and Viscum album subsp.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results correlate with those found in Geoffroea decorticans extracts, in which leaves showed higher levels of HCA derivatives when compared to stems [33]. Chapel [16], working with Calluna vulgaris (L.) Hull, reported that the higher amounts of polyphenolic compounds, including HCA, were found in stems and leaves at all phenological stages except during flowering, while no significant differences in PA content were observed among different organs and phenological stages. As in L. cuneifolia, PA were also found in adult plants of the Mexican mistletoes Phoradendron bollanum and Viscum album subsp.…”
Section: Discussionsupporting
confidence: 81%
“…Dobrecky [15] has also identified QE Production of secondary metabolites, including plant polyphenolics, depends on numerous factors, such as growth conditions (light, temperature, altitude, nutrient availability), plant phenological stage, and organ. Changes in the polyphenolic content are related to variations in the expression of the genes encoding the activity of enzymes involved in their biosynthesis [16]. Consequently, the analysis of polyphenolic compounds in different phenological stages and organs is relevant to increase the knowledge on polyphenol dynamics in L. cuneifolia and to harvest it at the highest levels of bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Biosynthesis of various phenolic compounds in plants depends on some factors, such as; species specificity, vegetation period, and growing conditions (climatic factors, water, light, altitude, and soil properties, etc.) (Chepel et al, 2020). Moreover, plants can produce various phenolic compounds at different growth stages and accumulate them in their bulb and/or other parts (Feduraev et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Reduced numbers of released T. colubriformis egg are found, although heather increases immunity to parasites [ 119 ]. When heather is fed to experimentally infected goats, it is associated with a reduction in the establishment of T. colubriformis larvae and a significant decrease in nematode egg excretion by the host [ 122 ]. The aerial components of heather have been studied during different growth stages; however, heather’s medicinal properties are mainly described in traditional medicine, the plant’s pharmacologic potential is a focus of current investigations.…”
Section: Plants Used In Traditional (Folk) Medicine In Latviamentioning
confidence: 99%
“…Heather herb possesses antioxidant activity, and its antibacterial effects are mediated by the leaf, stem, rhizome, and root extracts. Leaf and stem extracts inhibit the infectivities of Gram-positive and Gram-negative bacteria, and roots are active against Bacillus subtilis , and extracts of the rhizome are active against E. coli [ 122 ]. Further, combinations of the active substances and amounts differ according to the season and are higher during growth.…”
Section: Plants Used In Traditional (Folk) Medicine In Latviamentioning
confidence: 99%